Note—A Note on Dynamic Programming with Unbounded Rewards - van Nunen, J. A. E. E.; Wessels, J. (Management Science, 1978)
In a recent paper, Lippman presents sufficient conditions for Denardo's N-stage contraction in discounted semi-Markov decision processes with unbounded rewards. In this note it is demonstrated that Lippman's conditions may be replaced by weaker conditions which even imply 1-stage contraction. The verification of the conditions of this note is somewhat easier.